Reconciliation, Heritage and Social Inclusion in the Middle East and North Africa, edited by Iyad Muhsen AlDajani, and Martin Leiner. Springer, Cham. 2022. XXV, 481 pp. https://doi.org/10.1007/978-3-031-08713-4. - Vahram Petrosyan (Journal of Political Science: Bulletin of Yerevan University, 2022)
The idea of ​​reconciliation, heritage and social inclusion in the Middle East and North Africa has been in the spotlight for many decades, as both regions constantly present such dramatic changes that reverberate around the world. In both regions, the geopolitical interests of world and regional powers are closely intertwined, and energy reserves allow you to influence the level of prices for them. In fact, all this becomes the reason for the acute manifestation of religious conflicts, the politicization of religion and tradition, thereby creating a turbulent environment for many actors. It is also worth mentioning the unresolved issues of nation-building and nation-states, the diversity of the ethnic and religious composition of the population in many places, the uneven distribution of income in societies, the level of militarization, and much more, to present the complexity and anxiety of the overall picture.